GNA14, GNA11, and GNAQ Mutations Are Frequent in Benign but Not Malignant Cutaneous Vascular Tumors - Jansen, Philipp; Müller, Hansgeorg; Lodde, Georg C.; Zaremba, Anne; Möller, Inga; Sucker, Antje; Paschen, Annette; Esser, Stefan; Schaller, Jörg; Gunzer, Matthias; Standl, Fabian; Bauer, Sebastian; et al. (Frontiers in Genetics, 2021)
Cutaneous vascular tumors consist of a heterogeneous group of benign proliferations, including a range of hemangiomas and vascular malformations, as well as heterogeneous groups of both borderline and malignant neoplasms such as Kaposi’s sarcoma and angiosarcomas. The genetics of these tumors have been assessed independently in smaller individual cohorts of different ethnicities making comparisons difficult. In our study, we analyzed a representative cohort of benign vascular proliferations observed in a clinical routine setting as well as a selection of malignant vascular proliferations. Our cohort of 104 vascular proliferations including hemangiomas, malformations, angiosarcomas and Kaposi’s sarcoma were screened by targeted next-generation sequencing for activating genetic mutations known or assumed to be potentially relevant in vascular proliferations. An association analysis was performed for mutation status and clinico-pathological parameters. Frequent activating hotspot mutations in GNA genes, including GNA14 Q205, GNA11 and GNAQ Q209 were identified in 16 of 64 benign vascular tumors (25%). GNA gene mutations were particularly frequent (52%) in cherry (senile) hemangiomas (13 of 25). In angiosarcomas, activating RAS mutations (HRAS and NRAS) were identified in three samples (16%). No activating GNA or RAS gene mutations were identified in Kaposi´s sarcomas. Our study identifies GNA14 Q205, GNA11 and GNAQ Q209 mutations as being the most common and mutually exclusive mutations in benign hemangiomas. These mutations were not identified in malignant vascular tumors, which could be of potential diagnostic value in distinguishing these entities.